Pengaruh Kenaikan Berat Badan Rata – Rata Per Minggu pada Kehamilan Trimester II dan III terhadap Risiko Berat Bayi Lahir Rendah - Darmayanti Siswanto Agus Wilopo, Detty Siti Nurdiati (Berita Kedokteran Masyarakat (BKM), 2010)
Background: Low pregnancy weight gain is one of the risk factor of low birth weight (LBW). Weight gain rate per week can be used gain during pregnancy. However, some studies show differences in cut-off point weight gain in pregnancy of second and third trimester to minimize the risk of LBW.Objective: To identify changes of weight gain rate per week in the second and third trimester of pregnancy in relation to the risk of LBW.Method: The study was observational study using case control design. The study population was women giving birth at Ulin Hospital of Banjarmasin during the period of November 2006 – August 2007. Subject of the study was having LBW infants 98 mothers as case group and giving birth to infants >2500 grams 245 mothers as control group. Data medical record of obstetric and gynecology unit, mother and child health monitoring books, so did the direct interview. Chi square and double logistic regression methods were used to analyse the relationship between the objective variabels.Result: Weight gain <250 grams/week in the second and third trimester of pregnancy had significant relationship with the risk of LBW (OR 7.1; 95%CI 4.0 – 12.5): other variables having risks of LBW were gestational age (<37 weeks), hypertensive disorder during pregnancy, parity, having history of preterm delivery and prenatal care < 5 times. The result of multivariable analysis showed that weight gain <250 grams/week in the second and third trimester of pregnancy had significant relationship with LBW; other variables were preterm delivery, hypertensive disorder during pregnancy and primipara.Conclusion: Pregnant mothers with weight gain <250 grams/week during second and third trimester of pregnancy had probability 7.1 times of having LBW infants than those giving birth to infants >2500 grams. Other variables having risks of LBW were gestational age (<37 weeks), hypertensive disorder during pregnancy, parity, having history of preterm delivery and prenatal care < 5 times.Keywords: weight gain rate per week, low birth weight